1992
DOI: 10.1111/j.1464-410x.1992.tb15532.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DMSA Scintigraphy with Intravenous Urography for the Detection of Renal Scarring and its Correlation with Vesicoureteric Reflux

Abstract: A series of 208 patients was prospectively assessed for reflux nephropathy by intravenous urography (IVU) and 99mTc-dimercaptosuccinate (DMSA) scintigraphy. All patients were studied at least 3 months after their most recent urinary tract infection and micturating cystourethrography (MCU) was performed prior to the scintigraphic studies. DMSA scintigraphy detected significantly more cortical abnormalities than did IVU. There was also a correlation between cortical abnormalities in the DMSA studies and the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Similar results have been obtained from pig studies by Risdon et al [55]and Arnold et al [56]. The clinical studies supporting the accuracy of the DMSA for scars include those by Webb and Britton [57]and Elison et al [58]; the latter group conducted a prospective study of 208 patients which showed more anomalies on DMSA than on IVP, with good correlation of the DMSA findings with the degree of VUR. Monsour et al [59]assessed 150 children with IVP, ultrasound, and DMSA, finding 1.92 ± 1.92 scars on intravenous urogram, 2.79 ± 1.87 scars on ultrasound, and 3.82 ± 1.71 scars on the DMSA; these authors suggested an eight-part grading system for the renal scarring based on the DMSA appearance.…”
Section: Radiological Investigation Of Vurthe First Diagnostic Study supporting
confidence: 71%
“…Similar results have been obtained from pig studies by Risdon et al [55]and Arnold et al [56]. The clinical studies supporting the accuracy of the DMSA for scars include those by Webb and Britton [57]and Elison et al [58]; the latter group conducted a prospective study of 208 patients which showed more anomalies on DMSA than on IVP, with good correlation of the DMSA findings with the degree of VUR. Monsour et al [59]assessed 150 children with IVP, ultrasound, and DMSA, finding 1.92 ± 1.92 scars on intravenous urogram, 2.79 ± 1.87 scars on ultrasound, and 3.82 ± 1.71 scars on the DMSA; these authors suggested an eight-part grading system for the renal scarring based on the DMSA appearance.…”
Section: Radiological Investigation Of Vurthe First Diagnostic Study supporting
confidence: 71%
“…218 Half of these studies did not include an appropriate spectrum of patients. The quality of reporting was poor: the majority of studies (6/8) did not report patient selection criteria; 133,138,141,193,196,214 five studies provided inadequate description of the reference standard and/or the index test; 133,193,196,217,218 half of all studies did not report sufficient information to assess the avoidance of test review bias, 133,141,196,214 and four studies did not report sufficient information to assess avoidance of disease progression bias. 133,214,217,218 Disease progression bias was a problem in two studies 141,196 and partial verification bias in another study.…”
Section: Static Renal Imagingmentioning
confidence: 99%
“…Only half of the studies included an appropriate patient spectrum 133,193,196,214 and only two provided sufficient details on selection criteria. 217,218 Half of the studies reported that both test review bias and reference standard review bias had been avoided, 138,193,217,218 but only one study reported that the same clinical information was available when test results were interpreted as would be available in practice. 217 None of the studies provided an explanation as to why some of the children did not receive both the index test and reference standard.…”
Section: Static Renal Imagingmentioning
confidence: 99%
See 2 more Smart Citations